Upper Gastrointestinal Endoscopy at the Korle Bu Teaching Hospital, Accra, Ghana - Aduful, H.K.; Naaeder, S.B.; Darko, R.; Baako, B.N.; Clegg-Lamptey, J.N.A.; Nkrumah, K.N.; Adu-Aryee, N.A.; Kyere, M. (My University, 2007)
Objectives To study the indications for endoscopy, the endoscopic diagnosis and other lessons learnt. Methods A retrospective and prospective audit of all upper gastrointestinal endoscopies performed in the Endoscopy Unit of the Korle-Bu Teaching Hospital from January 1995 to December 2002 was performed. Results A total of 6977 patients, 3777 males and 3200 females with age range 1 year 8 months to 93 years were endoscoped. The mean age of males was 43.5 ± 0.5 and females 43.7 ± 0.6 years. Epigastric pain (42.5%), dyspepsia (32.8%) and haematemesis and melaena (14.2%) were the commonest reasons for endoscopy. Chronic duodenal ulcer (19.6%), acute gastritis (12.7%), duodenitis (10.2%), oesophagitis (7.5%) were the commonest diagnoses. Normal endoscopy was reported in 41.1% patients, and was higher in the younger age group compared to the older (R = 0.973, P<0.001). Nine hundred and ninety (14.2%) patients were endoscoped for haematemesis and melaena of which chronic duodenal ulcer (32.1%), gastritis/gastric erosions (12.8%), oesophageal varices (9.8%), carcinoma of the stomach (6.4%), and duodenitis (4.2%), were the commonest causes. No lesion was found in 20.6% of these patients. Urease test was positive in 75% of all biopsy specimen and 85% in chronic duodenal ulcer, gastritis and duodenitis. Conclusion The normal endoscopy rate is high and needs to be reduced in order to help prolong the lives of the endoscopes. Chronic duodenal ulcer is usually associated with H. pylori infection and is the commonest cause of upper gastrointestinal bleeding.
Keywords: Upper gastrointestinal bleeding, haematemesis, melaena